Tourism Industry In Malaysia And It's Contribution To Economy Development - Nagarajan, N. Renuga (2004)
The main purpose of this paper is to derive the importance of tourism sector to the economic development and the other factors influencing it. This study was carried out by using simple linear regression model. The collected data were tested on yearly basis. The focus of the study is to analyze against the tourist arrival pattern, tourist receipts, average expenditure per capita, accommodation expenses, shopping expenses, entertainment expenses and hotel occupancy by locality.